The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/cbf.1638
|View full text |Cite
|
Sign up to set email alerts
|

Bacoside A downregulates matrix metalloproteinases 2 and 9 in DEN‐induced hepatocellular carcinoma

Abstract: Cancer metastasis is a complex multi-step process, responsible for a majority of cancer-related deaths by affecting the critical organs and causing complications in therapies. Hepatocellular carcinoma is a multi-factorial disease and is the third most common cause of cancer related mortality worldwide. Clinical and experimental studies have shown that MMP-2 and MMP-9 are involved in tumor invasion and metastases and their elevated expression has been associated with poor prognosis. Our recent studies showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…DEN is one of the carcinogens to induce metastasis in HCC (Janani et al, 2010). MMP-9 plays an important role in tumor metastasis and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DEN is one of the carcinogens to induce metastasis in HCC (Janani et al, 2010). MMP-9 plays an important role in tumor metastasis and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that DEN used to induce tumor metastasis in rodents as a chemical-induced experimental model. It also has the ability to express MMP-9 in HCC (Janani et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with bacoside A demonstrated the delayed development and growth of neoplastic nodules. The levels of AFP, carcinoembryonic antigen (CEA), aspartate transaminase (AST), alanine transaminase (ALT), ROS, lipid peroxides, GSH antioxidant enzymes, SOD and CAT, vitamins A and E and MMP-2 and -9 were decreased in the bacoside A-treated rats [141,142] . Thoppil …”
Section: Diterpenesmentioning
confidence: 99%
“…Pennell [family: Scrophulariaceae ] has been considered as a reputable nootropic medicine and is traditionally used for memory enhancing, rejuvenating, increasing longevity and promoting progeny [4]. Experimental studies have shown that Bacopa monnieri possesses anti-dementia [5], cognitive enhancing [6, 7], antidepressant [8], anti-anxiety [9], antiepileptic [1012], antiparkinson [13, 14], anti-amnesic [1517], antibacterial [18], antidiabetic [19], anti-inflammatory [2022], anti-arthritis [23], antihypertensive [24], anticancer [25], anti-asthmatic [26], spasmolytic [27], antiulcer [28, 29], analgesic [30–32], anti-aging [33], antifungal [34], antioxidant [3537], adaptogenic [38, 39], anti-addictive [40, 41], lessened narcotics-induced toxicity [42], neuroprotective [35, 4345], antiemetic [46, 47], cardioprotective [48, 49], hepatoprotective [50–53] and nephroprotective [53, 54] properties. Clinical trials have shown that Bacopa monnieri has both acute [55, 56] and chronic [5559] cognitive enhancing effects and improves memory performance in older persons [60, 61] and patients with Alzheimer’s disease [62].…”
Section: Introductionmentioning
confidence: 99%